PELATIHAN “SELF AWARENEES” UNTUK MENURUNKAN INTERNAL PERSEPSI MENIKAH DINI - Haq, Akhmad Liana Amrul; Pambuko, Zulfikar Bagus (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This study aims to test the effectiveness of self-awareness training to reduce perceptions of early marriage. The subjects in this study were 6 people who were divided into two groups, 3 subjects were in the experimental group (given training) and 3 subjects were in the control group (not given training). . Data collection in this study used the internal scale of perceptions of early marriage and was analyzed using the non-parametric Mann-Whitney U technique. The results of the 2-group differential test using SPSS were Asymp values. Sig of 0.043 (p <0.05), this shows that "self-awareness" training is effective in reducing internal perceptions of early marriage. Subjects who attended training had lower internal perceptions than research subjects in the control group who did not attend training. The end result of this research process is the "self-awareness" training module which is designed as a form of intervention in reducing internal perceptions of early marriage that is feasible to use.